3
fx=3x-5 f=(3x-5)/x f2=(6x-10)/x /=divide
3
Are you trying to solve for x? Fx = x2 - 3 x2 - Fx - 3 = 0 x2 - Fx = 3 x2 - Fx + (F/2)2 = 3 + (F/2)2 (x - F/2)2 = 3 + (F/2)2 x - F/2 = ±[ 3 + (F/2)2 ]1/2 x = F/2 ± [ 3 + (F/2)2 ]1/2
If you are talking about f(x) then yes it is the same as y
3
fx=3x-5 f=(3x-5)/x f2=(6x-10)/x /=divide
f(x)=5x+2
3
Are you trying to solve for x? Fx = x2 - 3 x2 - Fx - 3 = 0 x2 - Fx = 3 x2 - Fx + (F/2)2 = 3 + (F/2)2 (x - F/2)2 = 3 + (F/2)2 x - F/2 = ±[ 3 + (F/2)2 ]1/2 x = F/2 ± [ 3 + (F/2)2 ]1/2
4. P'=P/a where Period of f(x) = P and period of f(ax) = P'
Yes
If you are talking about f(x) then yes it is the same as y
Negative the derivative of f(x), divided by f(x) squared. -f'(x) / f²(x)
Yes, when you read Fx aloud can you can shorten it to F of x.
a. 40 THE ANSWER IS 40 b. x c. 20 d. f(x)
f(71.19) = 71 where int(x) is the integer value of a number